PEMANFAATAN ABU KULIT BUAH KELAPA SEBAGAI KATALIS PADA REAKSI TRANSESTERIFIKASI MINYAK SAWIT MENJADI METIL ESTER - Muhammad Yusuf Ritonga, Doni Hermanto Sihombing, Allen Rianto Sihotang (Universitas Sumatera Utara, 2013)
Transesterification is the reaction to produce methyl esters in which this reaction’s catalyst involves coconut shell burnt ash at temperature of 550, 600, 650 °C for 8 hours and uses 1%, 2%, 3% (w/w) of ash. Ash used was dissolved in 75 ml of methanol to obtain potassium methoxide compound and was analyzed by AAS (Atomic Absorption Spectrophotometer) to determine potassium content. Palm oil involved in the processing stage of degumming with the addition of 0,6% (w/w) H3PO4 85% to remove gum then followed by an esterification reaction using 3,0% (w/w) H2SO498% as the catalyst to reduce FFA<1%. The temperature of transesterification reaction was at 65 °C for 2 hours, ratio of methanol: CPO 6:1 (n/n) and 500 rpm agitation. Quantitatively, the optimum yield of 81% methyl esters is gained with shell burnt ash at temperature of 600 ° C, 1% (w/w) of ash with the specification of methyl esters as density, kinematic viscosity and flash point are relatively conformed to SNI04-7182-2006 biodiesel and 92.99% purity methyl ester with 4.62% total glycerin,2.39% free glycerin based on GC (Gas Chromatography).